An improved Peukert battery model of nonlinear capacity considering temperature effect. Issue 31 (2018) - Zhang, Qi; Cui, Naxin; Shang, Yunlong; Duan, Bin; Zhang, Chenghui
Abstract: The traditional Peukert's law is mainly used for lead-acid batteries at constant discharge, however, it ignores the temperature effect on battery nonlinear capacity. Thus, it is not accurate enough for the remaining capacity estimation of lithium batteries when temperature changes. As to this problem, an improved Peukert battery model (PeBaM) considering temperature effect is proposed to describe the nonlinear capacity characteristic of lithium-ion batteries. The experimental battery module has a capacity of about 30 Ah, which consists of 20 battery cells connected in parallel. The available capacity of battery module was analyzed at different discharge current and temperature in MKL battery test system. It was verified that the maximum error of available capacity of the tested battery module is only 2.02% in the proposed PeBaM.